The effect of alcohol-containing mouthwash and alcohol-free mouthwash towards the power chains force decay - Santana, Willem; Thahar, Bergman; Mardiati, Endah; Salim, Jono (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
Introduction: Power chains is the common device used in fixed orthodontic treatment. Force decay in power chains is a problem that can affect the teeth movement due to a continuous force cannot be maintained. Force decay in power chain can be affected by the use of alcohol-containing mouthwash or alcohol-free mouthwash. The objective of this study was to determine the effect of alcoholic-containing mouthwash, alcohol-free mouthwash, and artificial saliva towards the power chains force decay. Methods: This research was an experimental analytic laboratory in-vitro with the comparative approach. The sample in this study were 40 power chain, short A (SA); 40 power chain, short B (SB); 40 power chain, long A (LA); and 40 power chain, long B (LB), which divided into 5 groups that were consecutively exposed to the artificial saliva as control group; Minosep® with 0.1% of chlorhexidine gluconate; Listerine® with 0% of alcohol; Hexadol® with 9% of alcohol; and Listerine® with 26.9% of alcohol. The measurement of force decay was performed with digital force gauge on day 0, 1, 14, and 28. The statistical analysis was done by using the Wilcoxon and Mann-Whitney tests. Result: There was a significant difference (p<0.05) between the force decay of power chain that exposed to the alcohol-containing mouthwash, alcohol-free mouthwash, and the artificial saliva. Conclusion: The force decay level of power chain that exposed to an alcohol-containing mouthwash was higher compared to the force decay level of power chain that exposed to an alcohol-free mouthwash and an artificial saliva.